IMAGE DAN PRE-IMAGE TRANSLASI PADA GRUP FUZZY INTUITIONISTIK - Dian Pratama (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2016)
A intuitionistic fuzzy set in is set gives a membership function and a non-membership function (the complement of membership function) for each with the sum worth one. When it’s applied in group’s theory, it will called intuitionistic fuzzy group with conditions membership function is fuzzy subgroup and non-membership function is anti-fuzzy subgroup. In this research, the operator will be given a fuzzy set is called fuzzy translation operator. This operator is a mapping imposed on membership functions (fuzzy subset) to interval [ 0,1]. This research will discuss the properties homomorphism of translation on intuitionistic fuzzy groups. These properties is the structure of the image and pre-image homomorphism of translation on intuitionistic fuzzy group. We obtain that image and pre-image of translation on intuitionistic fuzzy (normal) groups is also intuitionistic fuzzy (normal) groups.